Pre-service teachers’ beliefs about language teaching and learning: a longitudinal study (2013)
This paper contains the description of a research project that was carried out in the Bachelor of Arts in English Language Teaching program at a Mexican university. The study was longitudinal and it tracked fourteen students for four semesters of the eight semester program. The aim was to identify pre-service teachers’ beliefs about English language teaching and learning at different stages of instruction while they were taking the teaching practice courses in the program. The instruments employed were questionnaires and semi-structured interviews. The results demonstrated that students made links between theory and practice creating some changes in previous beliefs. The study revealed an increase of awareness and a better understanding of the complex processes involved in teaching and learning. En este artículo se describe una investigación que se llevó a cabo en el programa de Licenciatura en Enseñanza del Inglés de una universidad mexicana. El estudio fue longitudinal, el cual siguió la trayectoria de catorce estudiantes de la licenciatura durante cuatro de los ocho semestres del programa académico. El propósito fue identificar las creencias de estos maestros principiantes, quienes cursabansus clases de práctica docente del programa, acerca de la enseñanza y el aprendizaje del inglés en diferentes etapas de sus estudios. Los instrumentos utilizados fueron cuestionarios y entrevistas semiestructuradas. Los resultados demostraron que los estudiantes articularon la teoría con la práctica, lo cual incidió en sus creencias anteriores. El estudio también reveló que comprendieron mejor los complejos procesos involucrados en la enseñanza y el aprendizaje.